Fabrication of Ca(OH)2 nanostructures by facile solution – based synthesis at various reaction temperatures as CO2 adsorbent - Mohd Daud, Farah Diana; Sreekantan, Srimala; Mohamed, Abdul Rahman (Trans Tech Publications Ltd., 2013)
Calcium hydroxides (Ca(OH)2) nanostructures have been fabricated through simple facile solution based synthesis at different temperatures 35, 45 and 55°C repectively. Ethanol was utilized as a medium for reaction. The synthesized powder was characterized by Field Emission Scanning Electron Microscope (FESEM SUPRA 35VP ZEISS), Fourier transform infrared (FTIR Perkin Elmer Spectrum One Spectrophotometer) and X-ray diffraction (XRD). Based on XRD analysis, the synthesis samples exhibited crystal hexagonal phase of Ca(OH)2. The crystallite size for powders prepared was between 17 nm to 31 nm. Short nanorod like structures was successfully obtained in 80 ml ethanol solution for entire temperatures. However, the length and diameter decreased with increased the reaction temperatures. Short nanorod synthesized at 55°C has small diameters and length compared at 35°C. Carbon dioxide (CO2) adsorption for synthesized powders was studied by simultaneous thermal analyzer (STA). Ca(OH)2 prepared at 35°C and 45°C in 80 ml ethanol showed CO2 adsorption capacity about 9.3 mmol/g and 9.7 mmol/g respectively.